Modernism in the Lodz Ghetto: A Tentative Interpretation of Forgotten Holocaust Documents - Paweł Michna (Miejsce)
The author undertakes an initial analysis of the albums and posters produced in the Graphics Office of the Lodz Ghetto. Executed in a modernist style, with the use of photomontage techniques, the official propaganda documents—ordered by the Judenrat, headed by Chaim Mordechai Rumkowski—have not yet been the object of detailed research. Michna places them in the context of modern graphic design of the interwar period. Analyzing these materials as a precise medium for content, he treats them as an expression of mimicry—a survival strategy adopted by the Jewish ghetto authorities as part of the goal of turning the closed district of occupied Lodz into a rationally organized city-factory. He asks why this material has been overlooked and marginalized by researchers and considers the status of the documents. Drawing on Dorota Głowacka’s conception, he categorizes the material as a kind of “negative testimony”—a distorted image that may nevertheless help us see other aspects of the Holocaust and its commemoration.